La concentration spatiale relative de la criminalité et son analyse : vers un renouvellement de la criminologie environnementale - Brantingham, Patricia; Brantingham, Paul (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1994)
This particular article describes and applies one type of analysis borrowed from regional economics and regional planning to look at macro to micro patterns in criminal activity. The technique is called Location Quotients and is used to analyse the relative mix of crimes across areas. Location Quotients are shown to have their strongest potential in microanalysis of crime patterns. As an initial test of the technique's relativistic analytic value. Location Quotients for motor vehicle theft were calculated for several levels within a Canadian cone of resolution that descends from the provincial level to the individual level in the municipality of Burnaby, British Columbia.